Customer satisfaction on water supply at Merbok, Kedah / Faizzatul Balqis Muhamad Arif and Siti Azah Mohd Yusoff - Muhamad Arif, Faizzatul Balqis; Mohd Yusoff, Siti Azah (2019)
Customer satisfaction on water supply refers to the satisfaction of respondents about the water supply provided at their home and using for daily use. This study examined the relationship between customer satisfaction on water supply among the respondents. A survey was carried out from nine areas at Merbok, Kedah. A total of 344 usable questionnaire obtained out of 346 of questionnaire that has been distributed among respondents at residential area at Merbok, Kedah. The data obtained were analysed and the following findings were found out. The relationship between water quality and water quantity with customer satisfaction were further examined. All these relationships were found to be significance towards customer satisfaction on water supply. This study provides strong evidence on water quality and water quantity between customer satisfaction on water supply.